Impact of low iodine diets on ablation success in differentiated thyroid cancer: A mixed‐methods systematic review and meta‐analysis. (24th May 2022) - Herbert, Georgia; England, Clare; Perry, Rachel; Whitmarsh, Alex; Moore, Theresa; Searle, Aidan; Chotaliya, Sneha; Ness, Andy; Beasley, Matthew; Atkinson, Charlotte
Abstract: Background: Debate remains regarding whether to recommend a low iodine diet (LID) before radioactive‐iodine treatment and its duration and stringency. This mixed‐methods review aimed to determine if iodine status affects treatment success, the most effective diet to reduce iodine status, and how LID impacts wellbeing. Methods: Five electronic databases were searched until February 2021. An effectiveness synthesis (quantitative studies) and views synthesis (qualitative, survey, and experience‐based evidence) were conducted individually and then integrated. Quality assessment was undertaken. Results: Fifty‐six quantitative and three qualitative studies were identified. There was greater ablation success for those with an iodine status of <50 mcg/L (or mcg/gCr) compared with ≥250 (odds ratio [OR] = 2.63, 95% confidence interval [CI], 1.18–5.86, n = 283, GRADE certainty of evidence very low). One study compared <50 mcg/L (or mcg/gCr) to 100–199 and showed similar rates of ablation success (OR = 1.59, 95% CI, 0.48–6.15, n = 113; moderate risk of bias). People following a stricter LID before ablation had similar rates of success to a less‐strict diet (OR = 0.67, 95% CI, 0.26–1.73, n = 256, GRADE certainty of evidence very low). A stricter LID reduced iodine status more than a less strict (SMD = −0.40, 95% CI, −0.56 to −0.24, n = 816), and reduction was seen after 1 and 2 weeks. The main challenges were a negative impact on psychological health, over restriction, confusion, and difficulty for sub‐groups. Conclusions: Although a LID of 1–2 weeks reduces iodine status, it remains unclear whether iodine status affects treatment success as only a few low‐quality studies have examined this. LIDs are challenging for patients. Higher‐quality studies are needed to confirm whether a LID is necessary.